Suicide, Psychoactive Substances, and Homelessness: A Scoping Review - Dalvan Antonio de Campos; Adriano Alberti; Carlos Eduardo Seganfredo Camargo; Andréia Biolchi Mayer; João Batista de Oliveira Junior; Nayara Lisboa Almeida Schonmeier; Rose Lampert; Gabriela Kades; Bruna Becker da Silva; Graziela Marques Leão; Duanne Alves Pereira Crivilim; Ben Hur Soares; et al. (Brain Sciences, 2025)
Background/Objectives: The homeless population (HP) is a heterogeneous group characterized by the absence of stable and conventional housing, often relying on public spaces and deteriorated environments for shelter and survival, either temporarily or permanently. This group is exposed to multiple health vulnerabilities, with substance use disorder (SUD) identified as a significant risk factor for suicidal behavior. The aim of this study was to conduct a scoping review of the relationship between PAS use and suicide among homeless individuals. Methods: A comprehensive literature search was performed using five databases: PubMed, Scopus, SciELO, LILACS, and Google Scholar. Studies were selected based on their relevance to the topic, and data were extracted regarding substance use, suicide-related outcomes, and associated sociodemographic and clinical factors. Results: The findings indicated a strong association between PAS use and increased suicidal ideation and behavior among homeless individuals, particularly among youth, men, and women. Opioids and alcohol were the most frequently reported substances in this context. Additional factors such as unemployment, exposure to violence, social inequalities, and mental health disorders further exacerbated the risk of suicide in this population Conclusions: The reviewed literature underscores the urgent need for integrated, context-sensitive interventions addressing both substance use and mental health among the homeless. Tailored public health strategies focused on prevention, harm reduction, and psychosocial support are essential to reducing suicide risk and promoting overall well-being in this highly vulnerable group.